1996
DOI: 10.1128/jb.178.1.314-316.1996
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an anaerobically induced phosphoenolpyruvate-dependent fructose-specific phosphotransferase system and evidence for the Embden-Meyerhof glycolytic pathway in the heterofermentative bacterium Lactobacillus brevis

Abstract: Heterofermentative gram-positive bacteria are believed to metabolize sugars exclusively via the pentose phosphoketolase pathway following uptake via sugar:cation symport. Here we show that anaerobic growth of one such bacterium, Lactobacillus brevis, in the presence of fructose induces the synthesis of a phosphotransferase system and glycolytic enzymes that allow fructose to be metabolized via the Embden-Meyerhof pathway.Lactic acid bacteria are a group of gram-positive bacteria that characteristically lack cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…Owing to the presumed absence of a functional PTS, there seemed to be no obvious regulatory role for the ATP-dependent phosphorylation of HPr at Ser-46 in these organisms. Although the report about the absence of EI and EIIs from heterofermentative lactobacilli later turned out to be wrong (an L. brevis ptsHI operon has been cloned and sequenced) (193) and the presence of a fructose-specific PTS induced under anaerobic conditions has been established (772), it initiated the search for additional functions of P-Ser-HPr, one of them being the regulation of CCR.…”
Section: Role Of P-ser-hpr In Ccrmentioning
confidence: 99%
“…Owing to the presumed absence of a functional PTS, there seemed to be no obvious regulatory role for the ATP-dependent phosphorylation of HPr at Ser-46 in these organisms. Although the report about the absence of EI and EIIs from heterofermentative lactobacilli later turned out to be wrong (an L. brevis ptsHI operon has been cloned and sequenced) (193) and the presence of a fructose-specific PTS induced under anaerobic conditions has been established (772), it initiated the search for additional functions of P-Ser-HPr, one of them being the regulation of CCR.…”
Section: Role Of P-ser-hpr In Ccrmentioning
confidence: 99%
“…Interestingly, Bai et al (2) observed increased activity of this type of aldolase sensitive to EDTA in cell extracts from M. tuberculosis H37Rv under conditions of low-oxygen tension. In Bacillus subtilis and Lactobacillus brevis, increased levels of this enzyme were also observed under anaerobic conditions (17,24). Fba was not identified in the microarray study or in the proteome studies of the M. bovis BCG response to low-oxygen tension that did not include culture filtrates (4,10,25).…”
Section: Resultsmentioning
confidence: 99%
“…However, the physiological significance of this observation was questioned when in vivo studies conducted with Bacillus subtilis and Staphylococcus aureus failed to reveal appreciable HPr(ser-P)-mediated inhibition of PTS and non-PTS sugar uptake under conditions that were thought to generate HPr(ser-P) in vivo (5,6,17,18,26). On the other hand, extensive studies with vesicles of Lactococcus lactis, Lactobacillus brevis, Enterococcus faecalis, Streptococcus bovis, and Streptococcus pyogenes provided evidence that inducer exclusion (inhibition of sugar uptake) and/or inducer expulsion (stimulated efflux of preaccumulated sugar) were mediated by HPr(ser) phosphorylation (1,2,25,(28)(29)(30)(31)(32)(33)(34)(35). Moreover, Lodge and Jacobson (12) showed that intact cells of Streptococcus mutans exhibit elevated sugar uptake following carbon starvation, and this enhanced activity correlates with decreased 32 P labeling of an acid-stable HPr derivative and not with increased levels of the protein (see reference 9).…”
mentioning
confidence: 99%